Citizen Journalism as Postmodern Journalism - Nova Darmanto; Santi Delliana (Politeknik Negeri Media Kreatif, 2017)
The rise of Citizen Journalism cannot be separated from the emergence of new genres in the media;the State of Citizen Journalism is inseparable from technological developments. The presence of online media currently characterizes the rapid growth of information and communication technology. The internet is a digital media that has become a symbol in the advancement of computerized era knowledge that gave birth to new media. The emergence of the internet, technology with the basis of this communication had a significant impact on the rapid pace of development in aspects of information, including points of reportage and journalism. Establishment of Citizens Journalism is born for the emergence of online Journalism. Online journalism has developed the necessaryfoundation of the concept of citizen journalism where the activities of citizen journalism are carried out using technology Digital technology is a technology that no longer uses human or manual power. Digital systems are the development of analog systems. Digitalization tends to be an automatic operating system with a format that can be read by computers. The term postmodern journalism is a reaction to modern journalism. A shift is not always formed from the revolution. The change from contemporary to postmodernism is a gradual evolution, in a process that is continuous through various periods and times. Postmodernism criticizes modernism, which has resulted in the centralization and universalization of ideas in many fields of science and technology.